A Model of Strategic Targeted Advertising - Andrea Galeotti; José Luis Moraga-González (Center for Economic Studies and ifo Institute (CESifo), 2004)
We study a simultaneous move game of targeted advertising and pricing in a market with various consumer segments. In this setting we explore the implications of market segmentation on firm competitiveness. If firms are unable to target their ads on different consumer segments, a unique zero-profit equilibrium exists. By contrast, if firms employ targeted advertising, they can obtain positive profits. In equilibrium firms price very aggressively when they address the most profitable segment, quite gently when they target their ads on the least profitable segment and moderately aggressive when they advertise in the entire market.
Keywords: 330; segmentation; targeted advertising; oligopoly; price dispersion; price discrimination